(untitled) (Ustozlar uchun, 2025)
This article discusses the ongoing progress and challenges in English language teaching within Uzbekistan’s educational system, highlighting key strategies to enhance English proficiency among students. It advocates for modernizing the curriculum to prioritize communicative, student-centered approaches that emphasize listening, speaking, and writing skills, rather than focusing solely on grammar and vocabulary. The integration of technology and multimedia resources is also emphasized as a critical tool to engage students and improve language skills, particularly through online platforms and interactive content. Furthermore, the article explores the value of creating language immersion opportunities, such as study tours and exchange programs, to offer students real-world language practice. Public-private partnerships are identified as a means to bolster resources and teacher training, while the establishment of robust assessment and feedback systems is recommended to ensure students’ practical language skills are thoroughly evaluated. The article concludes by underscoring the need for cooperation between educators, policymakers, and the private sector to address these challenges and improve English education, ultimately meeting the demands of a globalized world.